1997
DOI: 10.1111/j.1525-1314.1997.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic evolution of diamond‐bearing and associated rocks from the Kokchetav Massif, northern Kazakhstan

Abstract: A B S TR A CT Representative diamond-bearing gneisses and dolomitic marble, eclogite and Ti-clinohumite-bearing garnet peridotite from Unit I at Kumdy Kol and whiteschist from Unit II at Kulet, eastern Kokchetav Massif, northern Kazakhstan, were studied. Diamond-bearing gneisses contain variable assemblages, including Grt+Bt+Qtz±Pl±Kfs±Zo±Chl±Tur±Cal and minor Ap, Rt and Zrn; abundant inclusions of diamond, graphite+chlorite (or calcite), phengite, clinopyroxene, K-feldspar, biotite, rutile, titanite, calcite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
135
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 37 publications
10
135
2
Order By: Relevance
“…Published analyses (Vavilov et al 1991;Shatsky et al. 1995;Zhang et al 1997;Hermann et al 2001;Zhang et al 2002a, b;Massonne 2003) show a large range of composition which arises from the changes of P-T conditions and the variability in protolith compositions. In a Ti versus Si diagram (Fig.…”
Section: Application To Natural Samples-discussionmentioning
confidence: 98%
“…Published analyses (Vavilov et al 1991;Shatsky et al. 1995;Zhang et al 1997;Hermann et al 2001;Zhang et al 2002a, b;Massonne 2003) show a large range of composition which arises from the changes of P-T conditions and the variability in protolith compositions. In a Ti versus Si diagram (Fig.…”
Section: Application To Natural Samples-discussionmentioning
confidence: 98%
“…The geological relationship between ultra -high pressure (UHP) pelitic schists and eclogites has been reported in many studies; however, there have been limited discussions on the ascending carrier (e.g., England and Holland, 1979;Platt and Wallis, 1991;Zhang et al, 1997;Kaneko et al, 2000). It seems that UHP metamorphic (UHPM) rocks rise rapidly from the upper mantle to the crust.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the study of Hacker and Peacock (1995), three papers-by Gebauer et al (1997), Duchêne et al (1997), and Rubatto and Hermann (2001)-have reported that the exhumation rate of Dora -Maira is 20 -30 mm/year. According to Zhang et al (1997) and Hermann et al (2001), Kokchetav UHPM rocks rose at a rate of approximately 10 -30 mm/year. Do-bretsov and Shatsky (2004) proposed extremely high uplift velocities of 60 -200 mm/year for the Kokchetav UHPM rocks; however, the exhumation mechanism has not yet been understood completely.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of the present work is to investigate the formation of OH defects in coesite and stishovite from a natural granitic material under experimental conditions that reflect a realistic geotherm of a subducting continental crust fragment. The experimental condition chosen here is based on natural examples such as the Dora Maira (Chopin 2003) and the Kokchetav (Zhang et al 1997) massifs. Finally, the results from the present study are compared to the defect inventory of quartz synthesized previously from the same starting material (Frigo et al 2016), to evaluate the potential of silica polymorphs as carrier for light elements (H, B, and Li) to the Earth's interior.…”
Section: Introductionmentioning
confidence: 99%